Bronchoscopic Airway Foreign Body Extraction without Using Optical Forceps - Hegde, Shalini (J Indian Assoc Pediatr Surg, 2018)
AIM: Airway foreign body (FB) is a very common pediatric surgical emergency. On certain difficult occasions, the extraction of FB with optical forceps (OFs) is difficult. These conditions create a life-threatening scenario. We present some of the alternative methods of FB extraction for these situations. PATIENTS AND METHODS: This is a retrospective case review of patients presenting to pediatric emergency with airway FB. All patients had a chest X-ray done before the procedure. Rigid bronchoscopy was performed in all patients for retrieval. RESULTS: A total of 20 patients (6 females) were successfully scoped. The age ranged from 1.5 years to 12 years (mean 3.5 years). Bronchoscopic removal was aided by dormia basket (DB) in 13, Fogarty's catheter (FC) in 6, and magnet aided removal in 1. Complete removal was achieved in all patients. CONCLUSIONS: We recommend that DB, FC, and a magnet should form an indispensable part of bronchoscopy set. The use of these alternative methods is successful and allows ventilation during the removal in contrast to removal by OFs. These should be kept as an option if retrieval is difficult.